2010
DOI: 10.3109/09537104.2010.481475
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of hormone replacement therapy on plasma and platelet antioxidant status and fatty acid composition in healthy postmenopausal women

Abstract: Oxidative stress is suggested to play an important role in the pathogenesis of cardiovascular disease (CVD). Various hormone replacement therapy (HRT) protocols are used to reduce the CVD risk in postmenopausal women. Recent studies found that HRT lowers lipid levels and improves vascular endothelial function in postmenopausal women. In this study the effects of HRT on plasma and platelet membrane fatty acid composition and the oxidant-antioxidant system in postmenopausal women are investigated. Blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…An increase in vascular oxidative stress in women after menopause has been reported in several studies [18][19][20]28]. Furthermore, hormone replacement therapy has been shown to improve oxidative stress status of postmenopausal women [18,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in vascular oxidative stress in women after menopause has been reported in several studies [18][19][20]28]. Furthermore, hormone replacement therapy has been shown to improve oxidative stress status of postmenopausal women [18,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Rosano et al [9] concluded in their review that the underlying mechanisms of these benefits are thought to be twofold: firstly, estrogens induce endothelial vasodilatation via the release of the messengers nitric oxide and prostacyclin [10] and, secondly, they buffer harmful coagulation effects thereby directly reducing atherogenesis [11]. Recently, Gokkusu et al [12] demonstrated that the latter may be brought upon by an HRT-induced decrease in the palmitic, stearic and oleic acid contents of platelet membranes and an increase of linoleic and arachidonic acid. Moreover, Signorelli et al [13] described intima-media thickness decreases after longtime HRT in a clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…During the female life cycle, the induction of reactive species by estrogens is thought to be important during the reproductive stage (Sipe et al 1994;Yager 2000;Russo et al 2003;Okoh et al 2011), but the significance of this phenomenon during and after the menopause stage is controversial. Some studies defend hormone replacement therapy in postmenopausal women, which includes estrogen intake as protection (Bednarek-Tupikowska et al 2004;Bednarek-Tupikowska et al 2006;Darabi et al 2010;Gokkusu et al 2010) while other researchers showed no improvement in healthrelated quality of life (Hays et al 2003;Sherman et al 2003), or even an increased risk for probable dementia in postmenopausal women aged 65 years or older and no prevention of mild cognitive impairment (Shumaker et al 2003), during estrogen plus progestin therapy. In summary, although some studies have demonstrated that estrogen has antioxidant properties (Borrás et al 2003(Borrás et al , 2010 and thus a protective effect on the body, an increasing number of studies have recently shown another activity of estrogens as important pro-oxidants at physiological concentrations (Sipe et al 1995;Yager 2000;Russo et al 2003;Okoh et al 2011).…”
Section: Introductionmentioning
confidence: 99%